Pengembangan four-tier diagnostic test untuk mengetahui pemahaman konsep peserta didik pada materi gerak lurus - Erwinsyah, Heru; Muhassin, Mohammad; Asyhari, Ardian (UNIVERISTAS PGRI MADIUN, 2020)
Conceptual understanding is important in learning that is closely related to cognitive abilities. The objective of this research was to develop a test instrumen namely four-tier multiple choice in order to describe concept of understanding, misunderstood the concept, misconception, and eror in appreciating linear displacement subject. Research design used was Resarch and Development (R&D) that followed the development model of Plomp consisting of three phase: preliminary research, development and prototyping phase,and assessment phase. The research was conducted at SMAN 16 Bandar Lampung. Data collcting technique used was test and questionnaire. The test was managed namely four-tier diagnostic test. analysis result of expert review at whole was within the percentage of 86% and wa proper categorization to be used as a test to measure students’ concept of under standing on linear displacement subject. The result of analysis on the research data showed that the percentage of students’ understanding level using four-tier multiple choice categorized into: 59% of understanding concept, 19% of misunder the concept, 15,33% of misconception, and 6,67% of eror.